2022
DOI: 10.1039/d2nj02872g
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fluorine substituents on the crystal structure and spin crossover behavior of the cation [MnIII(3,5-diHal-sal2323)]+ complex family with BPh4 anions

Abstract: The mononuclear Mn(III) cation spin-crossover complexes with Schiff base ligands 3,5-diF-sal2323 and 3,5-Br,F-sal2323 have been synthesized: [Mn(3,5-diF-sal2323)]BPh4 (1) and two polymorphic modifications (2 and 3) of [Mn(3,5-Br,F-sal2323)]BPh4. Their crystal structure...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…73 Our detailed studies on [Mn(X-sal 2 -323)](ReO 4 ) (X = 5 Cl, 1 ; X = 5 Br, 2 ; X = 3,5 Cl, 3 ; X = 3,5 Br, 4 ; and X = 5 NO 2 , 5 ) confirm the significant impact of the ligand substituent on the spin-state switching behavior of the manganese( iii ) center in a MnN 4 O 2 coordination environment, where the cooperative effect coming from the solid-state structural features plays a very important role. In addition, our comprehensive findings along with the similar manganese( iii ) complexes having an isostructural [Mn(X-sal 2 -323)] + unit with various counter anions (BPh 4 − , ClO 4 − , NO 3 − , PF 6 − , TCNQ 1.5 − , OTf − , NTf 2 − , and ReCl 6 − ) 57–87 (Tables S12–S17†) allow us to conclude the immense effect of the ReO 4 − counter anion on the spin-state switching feature of manganese( iii ) complexes in a MnN 4 O 2 coordination environment.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…73 Our detailed studies on [Mn(X-sal 2 -323)](ReO 4 ) (X = 5 Cl, 1 ; X = 5 Br, 2 ; X = 3,5 Cl, 3 ; X = 3,5 Br, 4 ; and X = 5 NO 2 , 5 ) confirm the significant impact of the ligand substituent on the spin-state switching behavior of the manganese( iii ) center in a MnN 4 O 2 coordination environment, where the cooperative effect coming from the solid-state structural features plays a very important role. In addition, our comprehensive findings along with the similar manganese( iii ) complexes having an isostructural [Mn(X-sal 2 -323)] + unit with various counter anions (BPh 4 − , ClO 4 − , NO 3 − , PF 6 − , TCNQ 1.5 − , OTf − , NTf 2 − , and ReCl 6 − ) 57–87 (Tables S12–S17†) allow us to conclude the immense effect of the ReO 4 − counter anion on the spin-state switching feature of manganese( iii ) complexes in a MnN 4 O 2 coordination environment.…”
Section: Resultsmentioning
confidence: 52%
“…54–56 Since then, many research groups including us have been exploring spin-state switching of the manganese( iii ) system in MnN 4 O 2 based on N 4 O 2 hexadentate Schiff base ligands. 57–87…”
Section: Introductionmentioning
confidence: 99%
“…There are a few exceptions to this: [Mn­(3-NO 2 -sal-323)]­BPh 4 ·2MeCN, [Mn­(3,5-diCl-sal-323)]­BPh 4 , , [Mn­(3,5-diBr-sal-323)]­BPh 4 , [Mn­(3,5-Br,X-sal-323)]­BPh 4 , , and [Mn­(3-OMe-5-NO 2 -sal 2 -323)]­NTf 2 ( 6b ). All of these exhibit more than one unique Mn 3+ site in the crystal structure as well as sterically demanding substituents on the ligand and also contain a large counterion.…”
Section: Resultsmentioning
confidence: 99%
“…Subject to these factors, SCO may become synergistic, and the octahedral configuration of the corresponding complexes will be distorted. 13,26,[30][31][32][33][34][35][36] The SCO might be associated with crystallographic phase transition, and in turn, the detailed SCO study has clarified phase-transition modes like stepwise and hysteretic.…”
Section: Introductionmentioning
confidence: 99%
“…When introducing two F or F and Br in positions 3 and 5 of the phenolate nucleus, [Mn(3,5-diF-sal-N-1,5,8,12)]BPh 4 and two polymorphic modifications [Mn(3,5-F,Br-sal-N-1,5,8,12)]-BPh 4 (monoclinic and triclinic) show different magnetic properties. 34 Monoclinic complexes [Mn(3,5-diF-sal-N-1,5,8,12)]BPh 4 and [Mn(3,5-F,Br-sal-N-1,5,8,12)]BPh 4 undergo a slow and complete SCO. However, triclinic [Mn(3,5-F,Br-sal-N-1,5,8,12)]BPh 4 stays in a HS state within 2-300 K. These results showed that different ligand substituents produced different ligand field strength and intermolecular interactions, which affected the synergistic effect and SCO behavior.…”
Section: Introductionmentioning
confidence: 99%